English Translation of Selection from Ojos Negros ('Black Eyes') by Eduardo Sguiglia - Erin S Finzer (Studies in 20th & 21st Century Literature, 2015)
This is an English translation of a pivotal segment of Eduardo Sguiglia's novel, Ojos negros ('Black Eyes').
Keywords: Ojos negros; Eduardo Sguiglia; literary translation; animal studies; environmental injustice; testimonial novel